Effect of sera from patients with rheumatoid arthritis on normal lymphocytes: a possible immunoregulatory role for immune complexes. Issue 6 (December 1982) - Highton, J; Panayi, G S; Shepherd, P; Wooley, P
Abstract : The ability of rheumatoid sera to support concanavalin-A transformation of normal lymphocytes was inversely related to serum C1q binding activity. When C1q binding activity of the sera was removed by absorption with staphylococcal protein A, subsequent lymphocyte response increased to the level found in immune-complex negative sera. Gel filtration of a small number of sera suggested that the suppressive material had a molecular weight in the range 1.8-4.9 x 10(5) daltons. Aggregated human gammaglobulin suppressed con-A transformation of normal lymphocytes in a dose-dependent fashion. These results suggest that immune complexes present in rheumatoid sera can suppress lymphocyte responsiveness. The relevance of this observation to be clinical features of rheumatoid arthritis is discussed.